IMPROVING TREATMENT OF ACUTE ADHESIVE INTESTINAL OBSTRUCTION IN PATIENTS WITH HEPATIC DYSFUNCTION - Ільїна-Стогнієнко, В.Ю. (World of Medicine and Biology, 2014)
Features of the clinical course, relapse of acute adhesive intestinal obstruction in patients with hepatic impairment is not investigated and classified, which greatly reduces the effectiveness of treatment. This work investigates the effectiveness of treatment of patients with acute adhesive intestinal obstruction and hepatic impairment by correcting processes of energy metabolism in the peritoneum. To this end, traditional postoperative treatment additionally administered drug of "Glutoxim" in conjunction with hepatoprotector "Essliver forte." Conducted analysis of long-term results of treatment for three years. Through the use of these treatment, macroergic providing peritoneal tissue increased by 32,7-50,0%, number of mesothelium cores high activity also significantly increased by 34.8%. Term restoration of motility decreased from 7,4±1,8 to 5,3±1,4 days (P
Keywords: acute adhesive intestinal obstruction; liver dysfunction; glutoxim; essliver forte